PERANAN H. BAHARUDDIN YUSUF SEBAGAI TOKOH PENDIDIKAN DI KOTA PEKANBARU TAHUN 1967-1996 - Alfy Ferissa; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: H. Baharuddin Yusuf is one of the figures in advancing education in Pekanbaru City. H.Baharuddin Yusuf has a desire to educate the younger generation and advance education, both general educationand islamic education. H. Baharuddin Yusuf has a role in advacing education in Pekanbaru City. As for the purpose of this study is to 1) Know the life history of H. Baharuddin Yusuf 2) To find out the role of H. Baharuddin Yusuf in advancing education 3) To find out what achievements H. Baharuddin Yusuf has achieved in advancing education. The method used in this reseach is qualitative method. Data collection techniques used are interview tecniques, lietarature and documentation. The place of research in writing this scientific paper is the city of Pekanbaru. The result of this study can be concluded that H. Baharuddin Yusuf was born in Pekanbaru on May 2, 1920. He has a role in advancing education starting from being a teacher and founder of the Nurul Falah Foundation. H. Baharuddin Yusuf in politics he becoming a member of the Pekanbaru City Council in the field of education, H. Baharuddin Yusuf also became the head of the Religious Affairs Inspection Office in Pekanbaru City. In advancing education, H. Baharuddin Yusuf has obstacles that make him more anthusiastic to achieve the goals he has planned.Key Words: H. Baharuddin Yusuf, Education in Pekanbaru City, Role